2018
DOI: 10.1021/acschemneuro.8b00204
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Learning as a Paradigm Shift in Brain Learning

Abstract: Experimental and theoretical results reveal a new underlying mechanism for fast brain learning process, dendritic learning, as opposed to the misdirected research in neuroscience over decades, which is based solely on slow synaptic plasticity. The presented paradigm indicates that learning occurs in closer proximity to the neuron, the computational unit, dendritic strengths are self-oscillating, and weak synapses, which comprise the majority of our brain and previously were assumed to be insignificant, play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This concept of spike-timing dependent plasticity (STDP) means that the learning scheme is global, strengthening the synapses that the backpropagating signal can reach. However, Sardi et al [1] proposed a paradigm shift in learning, that is, by dendritic learning instead of the slow synaptic plasticity. Recent experimental studies in CA3 pyramidal neurons prove that a single dendritic branch induces branch-constrained synaptic plasticity through NMDA spikes and Ca 2+ transients [72] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept of spike-timing dependent plasticity (STDP) means that the learning scheme is global, strengthening the synapses that the backpropagating signal can reach. However, Sardi et al [1] proposed a paradigm shift in learning, that is, by dendritic learning instead of the slow synaptic plasticity. Recent experimental studies in CA3 pyramidal neurons prove that a single dendritic branch induces branch-constrained synaptic plasticity through NMDA spikes and Ca 2+ transients [72] .…”
Section: Discussionmentioning
confidence: 99%
“…During simultaneous synaptic activation, the driving force of an input signal combines with the driving forces of its neighboring synaptic inputs. The contribution of a signal depends on several factors: its distance from the points of entry of other inputs, the diameter and length of its dendritic compartment, the morphology of the dendrites, the distribution of active channels, and the somatic dynamics, as well [1] [5] . If the sum of the driving forces reaching the somatic compartment is above the spiking threshold, an action potential (AP) is generated.…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic spines change shape as they mature, progressing from thin, to stubby to mushroom [95][96][97]. These changes in dendritic spine morphology correspond to their function of the brain and influence plasticity of the neuron, and ultimately the brain as a whole [98,99]. We have previously shown that COX-2 --KI male mice were less likely and COX-2 --KI females were more likely to have mature spines compare to the Saline control counterparts [39,56].…”
Section: Dendritic Spine Morphologymentioning
confidence: 99%
“…This ontogenic process is functionally analogous to the evolution of structural and positional diversity of dendrites as they have adapted to a spectrum of functional roles [5], e.g. the implementation of deep learning via synaptic plasticity [6,7]. Neurons are not, therefore, static structures, but rather can be regarded as undergoing continuous development throughout the life cycle.…”
Section: Introductionmentioning
confidence: 99%